Cyberstalking Victimization: An Empirical Assessment of RAT Among Female Iranian College Students - Kabiri, Saeed (Journal of interpersonal violence, 2022)
The role of routine activity theory (RAT) as a guiding theoretical approach to understand online victimization has been well documented. However, the recent emphasis in criminology on its applicability to online victimization has largely been based on evidence from Anglo-American studies. This study fills this gap by testing the predictive utility of RAT for cyberstalking victimization, using data from a sample of female Iranian students. Our structural equation model showed that online exposure to motivated offenders, target suitability, and ineffective online guardianship were positively and significantly associated with cyberstalking victimization. Our results provide strong support for RAT, indicating its generalizability to a different sociopolitical context.